Effectiveness of application for fluid replacement and blood management during surgery - ประสิทธิ์ศุภการ ศักดิ์กฤษณ์; Tachaudomdach, Chiraporn; Khorhongklang, Prasertsak (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
Fluid replacement and blood management are crucial roles of nurse anesthetists during surgery, significantly impacting patient survival. Developing an application to assist in fluid and blood management calculations is essential. This quasi-experimental research aimed to study 1) the effectiveness of a fluid replacement and blood management application during surgery and 2) nurse anesthetists’ satisfaction with the application. The sample included 39 nurse anesthetists from the anesthesiology department of Maharat Nakhon Ratchasima Hospital, selected through systematic sampling. Data collection tools consisted of a test and an opinion questionnaire, validated by six experts with a content validity index ranging from 0.83 to 1.00 and reliability ranging from 0.81 to 0.87. Data were analyzed using frequency distribution, percentage, mean, standard deviation, and paired t-test. The results showed that the average time for manual calculations was 4.09 minutes, while the application significantly reduced the calculation time to 0.22 minutes (p < 0.05, p = 0.00). Nurse anesthetists’ satisfaction with the application was at a highest level across all aspects (mean = 4.79 ± 0.40), including convenience, speed, accuracy, and applicability in both emergency and routine situations. This study demonstrates that the application effectively enhances operational efficiency and patient safety. Keywords: Fluid Replacement, Blood Management, Application